Antisynchronization of Nonidentical Fractional-Order Chaotic Systems Using Active Control - Sachin Bhalekar; Varsha Daftardar-Gejji (International Journal of Differential Equations)
Antisynchronization phenomena are studied in nonidentical fractional-order differential systems. The characteristic feature of antisynchronization is that the sum of relevant state-variables vanishes for sufficiently large value of time variable. Active control method is used first time in the literature to achieve antisynchronization between fractional-order Lorenz and Financial systems, Financial and Chen systems, and Lü and Financial systems. The stability analysis is carried out using classical results. We also provide numerical results to verify the effectiveness of the proposed theory.